Identifying obstacles encountered at different stages of the disaster management cycle (DMC) and its implications for rural flooding in Pakistan - Shah, Ashfaq Ahmad; Ullah, Ayat; Khan, Nasir Abbas; Shah, Muhammad Haroon; Ahmed, Rasheed; Hassan, Syed Tauseef; Tariq, Muhammad Atiq Ur Rehman; Xu, Chong (Frontiers in Environmental Science, 2023)
The world has seen a number of natural hazards, but among them, floods are perhaps the most frequent devastating natural hazard, resulting in more human causalities and financial losses. Rural inundation has grown into an issue of concern in various parts of the world, including Pakistan. Over the past few decades, it has been hard for local institutions and rural populations to recover from the trauma inflicted by these events. The disaster risk management cycle is a well-known tool for coping with disasters and their consequences. Yet, the DRM cycle efficacy has been questioned in various rural settings. Thus, this paper applied a programmatic strategy to understand the challenges disaster management authorities and communities face in managing flood risks through the conventional disaster management cycle in Khyber Pakhtunkhwa province, Pakistan. The study objective was accomplished by using both qualitative and exploratory research designs. Four communities with a historical record of flooding were chosen for focus group discussion (32 in total) using a purposive sampling method. 31 key informant interviews were undertaken from pertinent local disaster risk management institutions. We employed a thematic analysis to classify responses and obstacles into the various stages of the disaster management cycle. The findings of this study from interviews and focus groups provided some new insight into the conventional DRM cycle. The issues and challenges encountered by institutions and the community members were divided into four stages: 1-mitigation, 2-preparedness, 3-rescue and relief (R&R), and 4-rehabilitation and recovery (R&R). Based on the findings, it seems that local disaster management institutions still rely on reactive strategies and deal with flood hazards on an ad hoc basis. Poor governance and a lack of responses for present development trajectories were also highlighted as reasons why flood risk management is still challenging. There is an urgent need to perform susceptibility and risk assessments for multiple hazards and develop specialized plans that follow the principles of disaster risk reduction and adaptation to climate change. This study recommends incorporating resilience and adaptation to climate change into the current disaster management cycle to prevent or reduce future hazards and risks in rural areas.